Detection of Virulence Genes of Proteus Mirabilis Isolated from Clinical Samples of some Hospitals in Nasiriyah City - Amany Shakeir Jaber (Pakistan Journal of Medical & Health Sciences, 2022)
The study aimed to detect some virulence genes of Proteus mirabilis isolates, isolation and diagnosis by biochemical tests and Vitek-2 system . The research was conducted in Nasiriyah City/Dhi-Qar, Iraq, in the period between April 2021 and January 2022, and 70 urine and 30 wound samples were obtained from patients admitted to some Hospitals . Isolates diagnosis was made based on morphological and cultural characteristics of blood agar, MacConkey agar, as well as conventional biochemical tests and Vitek-2 identification system. Depending on these criteria, out of 100 samples bacterial growth appeared in only 80 (80.0%) samples, while no bacterial growth appeared in the remaining 20 (20.0%). only 20 (20%) isolates were obtained from P. mirabilis. chosen for genetic testing in order to detect the virulence factors (15) isolates from Proteus mirabilis, such as colonization factor antigen (CFA), extracellular protease, swarming activity, and urease, were identified. The results showed that all isolates (100%) possessed UreC gene, ZapA gene, flaA gene and mrp gene. Keywords: Proteus mirabilis, UTIs, UreC, ZapA, mrp and flaA